Digital transformation in German family firms : internal enablers and barriers for the development of dynamic capabilities for digital transformation - Olenhusen, Felix Carl Ferdinand Götz von (2019)
This dissertation investigates family firms' unique resources to sustain their competitive advantage over non-family firms. In addition, this work draws on the Dynamic Capabilities View to analyze sensing, seizing and transforming capabilities that are needed to cope with the challenges of digitalization. In this context, this dissertation explores how such dynamic capabilities apply to family firms when coping with digital transformation. Specifically, the work unveils family firms’ internal enablers and barriers for the development of dynamic capabilities for digital transformation. A qualitative research of ten case interviews with senior executives of German family firms across traditional industries has been conducted. This approach allowed to collect a broad scope of data to make sense of digital transformation in family firms. In addition, by applying the dynamic capabilities framework to the family firm context, the interviewees shared lived experiences on various activities of how family firms cope with digital transformation. The findings show that the definition, the scope and the emphasis of digital transformation depend on the size of the family firm. This study shows that for smaller family firms’ lack of strategic planning for digital transformation initiatives and digital innovation represent a crucial barrier for the development of dynamic capabilities for digital transformation. Furthermore, the findings indicate that the family firms' key differentiating resources, the organizational culture represented through exceptional commitment and loyalty of its human capital, and the allocation of its patient financial capital, represent critical barriers to cope with digital transformation.